High temperature corrosion in molten salts - Sequeira, C. A. C. (Molten salt forum ;, 2003)
Numerous commercial processes operate at temperatures exceeding 500 degrees Celsius. The materials used in high-temperature structures have design constraints which are in addition to those on materials used at, or near to, room temperature. These important additional constraints include time-dependent inelastic strain (creep), thermal stability of the microstructure and high-temperature corrosion. The addition of these constraints to those of low cost, strength, toughness, machinability, formability, weldability, and combinations of these, has led to the intensive development, over the past 50 years, of an extensive group of metallic materials: generally referred to as "high-temperature alloys". The purpose of the book is to provide chemical, metallurgical and materials scientists and engineers with up-to-date corrosion data pertinent to academic studies and industrial problems resulting from the effects of pure molten salt and ash/salt deposit environments. The book covers key aspects of corrosion reactions in molten deposits.